Transforming Nursing Practices: A Comprehensive Review of Performance Improvement Strategies - Vahideh Rostami; Nahid Hatam; Mohammad Amin Bahrami; Mahnaz Rakhshan; Azad Shokri (Health Science Reports)
ABSTRACT Introduction Nurses play a vital role in healthcare systems, directly influencing patient care quality and outcomes. This study aims to identify and analyze strategies for improving nursing performance in Iran through a systematic review and meta‐synthesis, following PRISMA 2020 guidelines. Methods Data were collected from four electronic databases: Web of Science, Scopus, PubMed, and Embase. Qualitative studies and mixed methods focused on nursing performance in Iranian healthcare contexts were included. Data management and theme development were facilitated using MAXQDA qualitative analysis software. Findings Thirty‐seven studies were included, identifying 10 key themes for improving nursing performance: leadership, organizational culture, self‐efficacy, mental health support, continuous education, technological integration, working conditions, performance evaluation, recruitment and retention, and service quality improvement. Conclusions A holistic approach, including leadership development, supportive work environments, continuous education, and technology integration, is essential for enhancing nursing performance and healthcare outcomes in Iran.